Muri-Q Method for Learning to Read, Memorize and Tahsin Al-Qur'an: A New Perspective - Abdul Fatah Bintoro; Imron Rosyadi; Muthoifin; Abdualhmeed Alqahoom (Walidem Institute and Publishing (WIP), 2023)
The objectives of this study are to: 1) Know the application of the muri-Q method at SDIT Muhammadiyah Al-Kautsar; 2) Know the results of the application of the muri-Q method at SDIT Muhammadiyah Al-Kautsar 3) Understand the obstacles to the application of the muri-Q method at SD Muhammadiyah Al-Kautsar. This type of research is descriptive qualitative using three data analyses. The methods used in this study are observation, interview, and documentation methods. The results of this study showed that the school implemented the muri-Q method every day with an allocation of time (30 minutes). The application of the muri-Q method in the tahfidz and Iqro' programs of students is grouped according to their group and classically. The obstacles faced in applying the Qur'anic tahfidz method are 1) Different abilities of children; 2) The influence of social media and electronic media; 3) Lack of murojaah; 4) The teacher does not have the capacity in the field of tahfidz and Iqro 'Al-Qur'an; 5) Lack of teachers in guiding tahfidz and Iqro learning The result of applying the muri-Q method to grade 2 is having memorized up to 1 juz and other achievements.